(NmETODY OBRABOTKI DANNYH RADIOFIZI^ESKOGO ISSLEDOWANIQ OKRUVA@]EJ SREDY (B/s - (NaRMAND(B, (NnEON aLEKSANDROWI^s; (NkRAPIWIN(B, (NwLADIMIR fEDOROWI^s; d; (NnELEPO(B, (Nb(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 258-266s
(NpREDM(B. (NUKAZ(B.: (NS(B. 267-268s
(Nan sssr(B, (NiN(B-(NT RADIOTEHNIKI I \LEKTRON(B.s
Keywords: (NmONITORING OKRUVA@]EJ SREDYs; (NfIZIKO(B-(NGEOGRAFI^ESKIE ISSLEDOWANIQs